The Geobacillus Pan-Genome: Implications for the Evolution of the Genus - Bezuidt, Oliver K.; Pierneef, Rian; Gomri, Amin M.; Adesioye, Fiyin; Makhalanyane, Thulani P.; Kharroub, Karima; Cowan, Don A. (Frontiers in Microbiology, 2016)
The genus Geobacillus is comprised of a diverse group of spore-forming Gram-positive thermophilic bacterial species and is well known for both its ecological diversity and as a source of novel thermostable enzymes. Although the mechanisms underlying the thermophilicity of the organism and the thermostability of its macromolecules are reasonably well understood, relatively little is known of the evolutionary mechanisms, which underlie the structural and functional properties of members of this genus. In this study, we have compared 29 Geobacillus genomes, with a specific focus on the elements, which comprise the conserved core and flexible genomes. Based on comparisons of conserved core and flexible genomes, we present evidence of habitat delineation with specific Geobacillus genomes linked to specific niches. Interestingly, our analysis has shown that horizontal gene transfer is a major factor deriving the evolution of Geobacillus from Bacillus, with genetic contributions from other phylogenetically distant taxa.